Les maniocs et les autres - Laure Emperaire (Revue d'ethnoécologie)
The apparent jumble of the Amerindian abatis of the Rio Negro is a materialization of spacialities, temporalities and social links operating on various scales. The biological diversity found there is based on mythical narratives, a long-term regional history, life courses, choices, necessities and expert knowledge. Its salient element is bitter cassava, Manihot esculenta Crantz, with numerous varieties, and the Rio Negro region is a well-known center of varietal diversification. However, these varieties of cassava come with many other starch supplying species that are consumed in different ways. These plants, whose role is dietary as much as it is social, are structured in several groups and one of which is made up of cassava companion plants. Do these different groups constitute a key to understanding the history of regional agriculture that would have operated through the accumulation of agrobiological diversity? It is on the basis of a reading grounded in mythical narratives, archeobotanical data, and an ethnographic approach to the plants having underground amylaceous reserves that we try to answer these questions.